Mobilizing the metropolis : how the Port Authority built New York - Plotch, Philip Mark, 1961-; Nelles, Jen, 1979- (University of Michigan Press, 2023)
The Port Authority of New York and New Jersey has morphed in ways that would be unrecognizable to its founders. Its mission evolved from improving rail freight to building motor vehicle crossings, airports, office towers, and industrial parks and taking control of a failing commuter rail line. In its early years, the agency was often viewed with admiration; however as it drew up plans, negotiated to take control of airfields and marine terminals, and constructed large bridges and tunnels, the Port Authority became the object of less favorable attention. It was attacked as a "super-government" that must be reined in, while the mayors of New York and Newark argued that it should be broken up with its pieces given to local governments for their own use. Despite its criticisms and travails, for over half a century the Port Authority overcame hurdles that had frustrated other public and private efforts, built the world's longest suspension bridge, and took a leading role in creating an organization to reduce traffic delays in the New York-New Jersey region. How did the Port Authority achieve these successes? And what lessons does its history offer to other cities and regions in the United States and beyond? In a time when public agencies are often condemned as inefficient and corrupt, this history should provide some positive lessons for governmental officials and social reformers. In 2021, the Port Authority marked its 100th birthday. Its history reveals a struggle between the public and private sectors, the challenges of balancing democratic accountability and efficiency, and the tension between regional and local needs. From selected Port Authority successes and failures, Philip Mark Plotch and Jen Nelles produce a significant and engaging account of a powerful governmental entity that offers durable lessons on collaboration, leadership, and the challenge of overcoming complex political challenges in modern America.